The Construction of Meaning through Physical and Inner Structures in the Poem "Aunty" by Tarida Ilham Manurung: A Structural Study by I.A. Richards - Tarida Ilham Manurung; Suci Amalia; Suci Ramadhani; Aisyah Syahfitri; Dini Apriani Siahaan; Rindu Purnama Sari; Intan Permata Sari Manurung (EDUJAVARE: International Journal of Educational Research, 2026)
Early Childhood Education (ECE) plays a fundamental role in supporting children’s cognitive, social, emotional, and physical development during the most critical years of life. This study aims to examine the physical and inner structures of the poem “Aunty” by Tarida Ilham Manurung using the perspective of I.A. Richards’ theory of poetry structure. This research employed a descriptive qualitative method with a formal structuralism approach. The data consisted of the intrinsic elements of the poem collected through careful reading and note-taking techniques. The analysis of the physical structure focused on diction, imagery, figurative language, rhythm, and rhyme, while the inner structure was analyzed through theme, feeling, tone, and message. The findings reveal that the physical structure of the poem is constructed through the selection of diction representing the geographical setting of Penang, the use of metaphorical expressions such as the symbol of “two shirts,” and the application of assonance rhyme with the vowel sound i, which creates a melancholic atmosphere through a descending rhythm. These elements strengthen the inner meaning of the poem, particularly in expressing themes of loss, longing, and the representation of a mother figure replaced by the figure of “Aunty” (Saadah Zainal Abidin). This study demonstrates that the integration of physical and inner structures plays an important role in constructing the aesthetic experience and emotional meaning of poetry. The implications of this research are expected to contribute to the development of literary criticism studies, particularly poetry appreciation learning in higher education, as well as enrich contemporary Indonesian literary studies.